Implementation of Microbial Fuel Cell in Harvesting Energy Using Wastewater - Noor Lina, Ramli; M. S., Abdul Wahab; S. A., Md. Sharif; N. H., Ramly (2015)
In this century, most of the company uses the electricity from the fossils fuels such as oil, gas and coal. This method will give negative impact to the environment and the fossils fuel will be run out. This project is to develop a microbial fuels cell that can produce electricity. There are several types of the microbial fuel cell, which are single chamber, double chamber and continuous. In this paper, the double chamber microbial fuel cell was selected to investigate the effect of suspended sludge into the double chamber microbial fuels cell. The salt bridge will construct between both chambers of the double chamber microbial fuels cell. Carbon graphite rod is selected as electrode at the cathode and anode to transfer the electron from anode to cathode. Electricity is generated from the anaerobic oxidation of organic matter by bacteria. At the end of this project, the microbial fuels cell was successful to generate electricity that can be used for a specific application.